Investigation of Esophageal Sensation and Biomechanical Properties in Functional Chest Pain - Nasr, Issam (2010)
OBJECTIVES: There is limited and conflicting data regarding the role of esophageal hypersensitivity in the pathogenesis of functional chest pain (FCP). We examined esophageal sensori-motor properties, mechanics and symptoms in subjects with FCP. METHODS: Esophageal balloon distension test (EBDT) was performed using impedance planimetry in 189 (m/f = 57/132) consecutive subjects with noncardiac, non-reflux chest pain, and 36 (m/f = 16/20) healthy controls. The biomechanical and sensory properties of subjects with and without esophageal hypersensitivity were compared to controls. The frequency, intensity and duration of chest pain were assessed. RESULTS: 143 (75 %) subjects had esophageal hypersensitivity and 46 (25%) had normal sensitivity. Typical chest pain was reproduced in 105/143 (74%) subjects. Subjects with hypersensitivity demonstrated larger cross-sectional area (CSA) (p<0.001), decreased esophageal wall strain (p<0.001) and distensibility (p<0.001), and lower thresholds for perception (p<0.01), discomfort (p<0.01) and pain (p<0.01) compared to those without hypersensitivity or healthy controls. Chest pain scores (mean ± SD) for frequency, intensity and duration were 2.5 ± 0.3, 2.2 ± 0.2 and 2.2 ± 0.2 respectively, and were similar between the two patient groups. CONCLUSIONS: 75% of subjects with FCP demonstrate esophageal hypersensitivity. Visceral hyperalgesia and sensori-motor dysfunction of the esophagus play a key role in the pathogenesis of chest pain.